Behaviour change interventions to reduce risky substance use and improve mental health in children in care: the SOLID three-arm feasibility RCT - Hayley Alderson; Eileen Kaner; Rebecca Brown; Denise Howel; Elaine McColl; Deborah Smart; Alex Copello; Tony Fouweather; Ruth McGovern; Heather Brown; Paul McArdle; Raghu Lingam (NIHR Journals Library, 2020)
Background: Looked-after children and care leavers (henceforth children in care) are young people placed under the care of local authorities, often because of a history of family abuse and/or neglect. These young people have significantly increased risk of substance use and mental health problems compared with peers. Aim: The Supporting Looked After Children and Care Leavers In Decreasing Drugs, and alcohol (SOLID) trial aimed to investigate the feasibility of a definitive randomised controlled trial comparing two behaviour change interventions to reduce risky substance use (illicit drugs and alcohol) in and improve the mental health of children in care aged 12-20 years. Methods: The study consisted of two phases: (1) a formative phase that adapted the motivational enhancement therapy and social behaviour and network therapy interventions for use with children in care and (2) a three-arm pilot randomised controlled trial (comparing motivational enhancement therapy, social behaviour and network therapy and usual care), and a linked process and economic (return on investment) evaluation. Trial feasibility was compared with prespecified STOP/GO criteria. Setting: Six local authority areas in the north-east of England. Participants: Children in care (aged 12-20 years) who screened positive for drug and/or alcohol use within the last 12 months were eligible for the trial. The formative and process evaluations included children in care, carers, social workers, and drug and alcohol workers. Outcome measures: The primary outcomes were recruitment and retention rates at 12 months' follow-up. Baseline and 12-month follow-up questionnaires measured self-reported drug and alcohol use, mental health and health-related quality of life. The process evaluation considered acceptability and engagement with the interventions and trial procedures. Results: Formative findings (n = 65) highlighted the need for interventions to increase the emphasis on therapeutic relationships, use creative methods of engagement and support the identification of treatment goals wider than substance misuse. Within the randomised controlled trial, of 860 participants screened, 211 (24.5%) met the inclusion criteria. One hundred and twelve (53%) of the 211 eligible children were recruited and randomised. Just 15 of the 76 (20%) participants allocated to intervention attended any of the motivational enhancement therapy of social behaviour and network therapy sessions, and 60 (54%) participants completed the 12-month follow-up. The screening and recruitment of children in care required significantly more time and resource investment by researchers and children's services than planned. The process evaluation (n = 116) demonstrated that, despite participants engaging in risky substance use, they did not often acknowledge this nor felt that they needed help. Children in care had complex, chaotic lives and children's services departments were less research mature and extremely stretched; this, coupled with the multiple steps in the intervention pathway and study protocol, resulted in low adherence to the intervention and the trial. Conclusions: The SOLID trial demonstrated successful engagement with children in care to adapt the motivational enhancement therapy and social behaviour and network therapy interventions. However, the pilot randomised controlled trial found that a definitive trial is not feasible. The current screen, refer and treat pathway for children in care did not work. There is an urgent need to radically rethink how we deliver therapeutic services for children in care. A pragmatic evaluation design, coupled with additional research resource for children's services, is needed to evaluate these novel models of care at scale. Trial registration: This study is registered as PROSPERO CRD42018098974 and Current Controlled Trials ISRCTN80786829. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 13. See the NIHR Journals Library website for further project information.